2003
DOI: 10.1097/00000542-200303000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Approximate Entropy, Bispectral Index, and Spectral Edge Frequency 95 (SEF95) with Clinical Signs of “Anesthetic Depth” during Coadministration of Propofol and Remifentanil

Abstract: Approximate entropy revealed informations on hypnotic and analgesic endpoints using coadministration of propofol and remifentanil comparable to bispectral index, SEF95, and the combination of drug concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(88 citation statements)
references
References 0 publications
2
84
0
2
Order By: Relevance
“…A comprehensive description of the calculation algorithm of state and response entropy has recently been published [9]. Several studies have validated the ability of entropy to measure the hypnotic component of anaesthesia with either volatile or intravenous anaesthetics [10][11][12][13]. The primary objective of this randomised controlled trial was to evaluate the impact of entropy monitoring on consumption of anaesthetics, conduction of anaesthesia and recovery times compared to standard clinical practice during total intravenous anaesthesia with two very shortacting drugs.…”
mentioning
confidence: 99%
“…A comprehensive description of the calculation algorithm of state and response entropy has recently been published [9]. Several studies have validated the ability of entropy to measure the hypnotic component of anaesthesia with either volatile or intravenous anaesthetics [10][11][12][13]. The primary objective of this randomised controlled trial was to evaluate the impact of entropy monitoring on consumption of anaesthetics, conduction of anaesthesia and recovery times compared to standard clinical practice during total intravenous anaesthesia with two very shortacting drugs.…”
mentioning
confidence: 99%
“…They have in common a lack of sensitivity to certain anaesthetics, e.g. nitrous oxide, and vary dependably though differently with halogenated anaesthetic vapours and propofol [2][3][4][5][6][7][8]. The primary aim of the present study was to compare, pair-wise, the degree of agreement in index values displayed by three commercially available depth-ofanaesthesia monitors during CPB for coronary artery bypass grafting (CABG).…”
mentioning
confidence: 99%
“…Approximate entropy can quantify the irregularity of data time series, i.e., the predictability of subsequent amplitude values based upon the knowledge of the previous amplitude values. Entropy of the EEG measures the regularity of the signal: high levels of entropy during anesthesia demonstrate that the subject is awake, whereas low levels of entropy correlate with deeper unconsciousness (Anderson et al , 2004, Bruhn et al , 2003, Hans et al , 2005, Vakkuri et al , 2004.…”
Section: Approximate Entropy (Apen)mentioning
confidence: 99%
“…Researchers have demonstrated that LZC and ApEn can distinguish between awake and anaesthetized state of human subjects (Anderson, Barr, 2004, Bruhn, Bouillon, 2003, Ferenets et al , 2006, Ferenets et al , 2007, Hans, Dewandre, 2005, Kumar et al , 2007, Noh et al , 2006, Vakkuri, Yli-Hankala, 2004, Voss et al , 2006, Zhang, Roy, 2001). In sleep research ApEn was statistically significantly lower during Stage IV and higher during wake and REM sleep (Burioka et al , 2005, Papadelis et al , 2007.…”
Section: Clinical Application Of Nda Correlated With Unconsciousnessmentioning
confidence: 99%